EVALUATION OF TIME AND COST PERFORMANCE ON THE GX OFFICE & CO WORKING BALI PROJECT USING THE EARNED VALUE METHOD - Rohim, Abd.; Witjaksana, Budi; Tjendani, Hanie Teki (Asosiasi Dosen Muda Indonesia, 2024)
In rapid construction developments, delays still occur frequently and have not been resolved, as experienced by the GX Office & Co Working Bali project. The project will be completed in 42 weeks, but in the 27th week, there is an indication of a delay of -4.31% from the initial plan. Earned Value Method (EVM) is a time and cost performance assessment method that can be used to develop strategies to minimize delays. This research aims to evaluate the time and cost performance of the GX Office & Co Working Bali project using the EVM method. A quantitative approach is used to collect and analyze project schedules, actual costs, and progress reports. EVM key indicators such as Planned Value (PV), Earned Value (EV), and Actual Cost (AC) are analyzed to determine Schedule Variance (SV), Cost Variance (CV), Schedule Performance Index (SPI), and Cost Performance Index (CPI). The results showed that the project experienced delays, especially from week 1 to week 14 and week 19 to week 27, with SPI values mostly below 1. However, the project showed increased efficiency in cost management with values CPI above one after week 14 to week 27, indicating that the actual costs incurred are lower than the value of the work completed. These findings highlight the need for corrective actions and more effective management strategies to address delays efficiently in terms of costs.